Critical analysis of lecturer’s perception on integrating concepts of sustainability in university curricular - Gunawardana, Anupama; Arooz, F.R.; Peramunugamage, A.; Halwatura, R.U. (Integrated Science Education Journal, 2020)
Purpose of the study: The growing emphasis on incorporating sustainability concepts in tertiary education has lead higher education institutions in developing countries to infuse sustainability content into their curricula. The wider purpose of this study is to promote the integration of sustainability concepts within Sri Lankan Universities. The study uncovers and presents the perception of university academics on integrating sustainability in higher education. Methodology: An online-survey was carried out in the month of January, 2019 at the University of Moratuwa, Sri Lanka across four faculties; engineering, architecture, information and technology and business. A descriptive analysis was employed to present the perceptions of the respondents according to different faculties. The obtained data were analyzed using Microsoft excel. Main Findings: Results revealed, 46.93% have already integrated sustainability concepts while 59.18% are willing to integrate in the near future. 80% have perceived that university curriculum should improve, according to the country’s need while providing particular trainings. 60% felt that knowledge and skills in ICT should be developed and adequate human resources should be deployed prior to incorporate sustainability concepts. Applications of this study: This study is aimed to identify models for mainstreaming sustainability concepts across the tertiary education in Sri Lanka. Novelty/Originality of this study: analyzing the perception of university lecturers on incorporating sustainability concepts across the university curricular, has never conducted in a Sri Lankan university. This is manily conducted to identify the gaps pertaining on intergrating sustainability concepts across university curricular and to identify the barriers exciting for education for sustainable development in Sri Lankan context.